Persepsi Karyawan Perempuan Terhadap Posisi Account Officer (Studi pada karyawan perempuan di PT BRIsyariah Kantor Cabang Madiun) - Yulia Anggraini (ACTIVA: Jurnal Ekonomi Syariah, 2018)
The position of the Account Officer is a very important position in the banking industry, the position of Account Officer at PT Bank BRIsyariah Tbk Madiun Branch Office is in addition to the task of finding financing customers, handling the provision of financing and supervising and controlling payments from the financing that has been provided based on sound financing feasibility so it is very good relationships with customers are needed. This position is also a ladder to become a permanent employee (the initial entry is as a contract employee) even this position is important to occupy a higher position. However, the conditions in the field, the very strategic position of Account Officers are dominated by men. This research was conducted at BRIsyah Syariah Madiun Branch Office and focused on female employees who were not in the Account Officer position. Data collection techniques were carried out by in-depth interviews which were then analyzed inductively. Based on the results of the study, it was explained about the perception of women who are in positions not account officers about the position. The researcher found a uniform answer from five female employees in the Customer service position, Teller and Administration and can be identified and analyzed the causes of the gender gap in the position of this Account Officer.